Evaluation of Nutritional Quality of Processed Livestock Products of Micro, Small and Medium Enterprises in North Bengkulu Regency - Fenita, Yosi; Santoso, Urip; Hardianta, M . Dodi; Fitri, Linda; Damayanti, Rossa; Hambali, Imam; Azis, Arif Rahman (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
The purpose of this study was to evaluate the quality of processed livestock products from Micro, Small and Medium Enterprises (MSMEs) in North Bengkulu Regency. The research location was MSME located in Kota Argamakmur. A total of 6 samples of processed livestock products were selected with 3 replications for each sample. All samples were measured nutritional composition and microbial counts. All data were processed using descriptive statistical methods. Furthermore, a comparative analysis was conducted to compare the nutritional composition profiles between types of processed products. For meatball and nugget products, a direct comparative analysis was conducted by comparing the average test results with the quality requirements listed in SNI 3818:2014 and the reference SNI 6683:2014. The results showed that the protein content of liver-gizzard, meatball, nugget, otak-otak, sempol (1) and sempol (2) were 28.50%, 7.20%, 11.93%, 14.83, 9.43 and 9.10, respectively. The fat content of liver and gizzard were 3.50%, 8.87%, 18.50%, 4.50%, 12.13%, and 12.50%, respectively, the Nitrogen Free Extract content was 0.37%, 10.60%, 10.23%, 10.03%, 14.20%, and 13.07%, respectively, and the crude fiber content was 0.53%, 1.33%, 1.76%, 0.90%, 1.43%, and 1.53%, respectively. The meatball did not meet the Indonesian National Standards (SNI), whereas the nuggets met SNI. It could be concluded that the liver and gizzard product contains the highest protein content, while the nuggets contain the highest fat content. The quality of meatballs needs to be improved to meet the minimum SNI, whereas nuggets have met SNI standard.